ANALISIS YURIDIS TERHADAP NOTARIS YANG BERTINDAK SEBAGAI PERANTARA BERKAITAN DENGAN JUAL BELI TANAH - RISMA ERNAWATI S (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. SUNARMI 2. DEDI HARIANTO3. T. KEIZERINA DEVI A The notary acting as an intermediary relating to the sale and purchase ofland violates the provisions of UUJN, Oath of Notary Public, and Notary Code ofConduct, for violating the principle of impartiality which may affect the honorand dignity of the notary. From that case the Regional Board should report to theRegional Honor Board that there has been a violation of the Code of Conductconducted by its members. Furthermore, the Regional Honorary Board shall takeimmediate action by holding a session of the Regional Ethics Council to discussallegations against such violations. The Notary Supervisory Board and theSupervisory Board of Notary shall conduct guidance and supervision of a notarypublic, by conducting notarial notary by the Notary Organization in order thatUUJN, Notary Oath Notary, and Notary Code of Conduct can be enforced.Keywords: Notary, Intermediary, UUJN, Oath of Official Notary, and Code ofConduct Notary Public1. PROF. DR. SUNARMI, SH,MHUM 2. DR. DEDI HARIANTO, SH, MHUM 3. DR. T. KEIZERINA DEVI A, SH,CN,MHUM